When virtual is more than real - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
When virtual is more than realLike many other institutions, CTA is creating a virtual library, for agriculture and rural development. It will make available in electronic virtual form the best of the technical and project information which...